Synthesis and color performance of CaCoSi2O6 pyroxene, a new ceramic colorant. (September 2015) - Mantovani, Luciana; Tribaudino, Mario; Dondi, Michele; Zanelli, Chiara
Abstract: The pyroxene structure was successfully used as a crystalline host for a new Co-based pink pigment. Different compositions of Ca1−x Co1+x Si2 O6 (0 ≤ x ≤ 1) powders were prepared by using the solid state method with different temperatures and times of annealing. The characterization of the fired samples was performed by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), colorimetry and technological tests simulating the ceramic applications. A monophasic pink clinopyroxene was obtained for compositions close to the CaCoSi2 O6 end-member. For increasing cobalt content, an assemblage of Co-olivine, Co-åkermanite and Ca, Co-pyroxene was found. Samples containing Co-åkermanite have a deep blue color stemming from Co 2+ in tetrahedral coordination, while those with Co-olivine are violet due to Co 2+ in octahedral coordination. The best conditions for the synthesis of a CaCoSi2 O6 single phase were then investigated, finding that a proper annealing cycle at 1150 °C prevents the formation of metastable Co-åkermanite. The CaCoSi2 O6 pyroxene was tested as a ceramic pigment into glazes and glassy coatings. In most cases, it behaves like a dye, completely dissolving in the melted glaze, analogously to Co-olivine. Graphical abstract: Highlights: Different compositions of Ca1-x Co1+x Si2 O6 (0 ≤ x ≤ 1) powders were prepared by using the solid state method. Among the different composition a monophasic pink pyroxene (CaCoSi2O6 ) was obtained. The pink pyroxene (CaCoSi2 O6 ) was subjected to technological tests and color analysis. We found that it behaves like a dye, completely dissolving in the melted glaze.